PEACE model of investigative interviewing - Šebek Vladimir (NBP: Nauka, bezbednost, policija, 2016)
During 1991, the British Home Office established a working group tasked with investigating and developing skills of interviewing witnesses, victims of crime and especially with suspects. The working group's efforts resulted in a model of investigative interviewing which provided a more efficient and ethical alternative to the up-to-date practice. The model presented in this paper became known as the PEACE, based on an acronym representing the five phases of this investigative interviewing method. The PEACE model was designed for conducting investigative interviews in all situations and with any type of interviewee, which makes it universal (regardless of being created for the territory of England and Wales) and certainly useful for police officers, especially those engaged in investigations of crimes (criminal investigations police). Also, due to its approach to this matter, the presented model builds a structure suitable for the work of other entities such as public prosecutors, judges, attorneys. The fact that the PEACE model is in use for over two decades speaks in favor of the positive results this methodology of work provides in investigative interviewing.